2016
DOI: 10.1002/anie.201510618
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Based Fuels: A Power‐to‐Fuel‐to‐Power Analysis

Abstract: alternative fuels ·c hemical hydrogen storage · energy conversion ·n itrogen ·nitrogen-based fuels

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 69 publications
(113 reference statements)
1
34
0
Order By: Relevance
“…However, renewable hydrogen from electrolysis could be used instead while ensuring a satisfactory stability of the Haber-Bosch process [6]. Grinberg Dana et al showed that NH 3 exhibits the highest Power-to-Fuel-to-Power ratio when compared with methane, methanol and dimethyl-ether [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, renewable hydrogen from electrolysis could be used instead while ensuring a satisfactory stability of the Haber-Bosch process [6]. Grinberg Dana et al showed that NH 3 exhibits the highest Power-to-Fuel-to-Power ratio when compared with methane, methanol and dimethyl-ether [7].…”
Section: Introductionmentioning
confidence: 99%
“…Further options of interest for combustion applications are being proposed, e.g., those derived from energy vectors such as NH 3 . Grinberg Dana et al [43 , 44] consider nitrogen-based fuels in non-toxic, safe-to-handle aqueous solutions such as ammonium nitrate-based compositions including ammonium hydroxide or urea. The authors have compared seven synthetic fuels, namely methane, methanol, DME, ammonia, and such nitrogen-containing aqueous fuels in terms of a power-to-fuel-to-power assessment [43] .…”
Section: Setting the Stage: Combustion And Chemistry In Contextmentioning
confidence: 99%
“…Grinberg Dana et al [43 , 44] consider nitrogen-based fuels in non-toxic, safe-to-handle aqueous solutions such as ammonium nitrate-based compositions including ammonium hydroxide or urea. The authors have compared seven synthetic fuels, namely methane, methanol, DME, ammonia, and such nitrogen-containing aqueous fuels in terms of a power-to-fuel-to-power assessment [43] . This methodology relates the available output power by the fuel's combustion to the energy required for its production (considering air separation, water splitting, and fuel synthesis) and distribution.…”
Section: Setting the Stage: Combustion And Chemistry In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…While a molecular catalyst for NH 3 production may never be efficient enough to replace the highly optimized Haber-Bosch process, research in this area results in valuable insights into the fundamental principles and electronic structure requirements for N 2 activation. This in turn may not only be relevant for fertilizer production, but also for alternative fuels that are based on nitrogen instead of carbon (Schlögl, 2010) (Grinberg et al, 2016; Chen et al, 2018). Catalysts that produce ammonia from dinitrogen are based on molybdenum, iron and cobalt (Roux et al, 2017), with many more elements known to be capable of binding N 2 and activating the strong N-N bond (Burford and Fryzuk, 2017; Klopsch et al, 2017).…”
Section: Introductionmentioning
confidence: 99%